Tellurium Chemistry (De Gruyter STEM, 2022)
Tellurium, a well-known chalcogen, finds potential applications in various fields from chemistry to other branches of science such as nanotechnology and macromolecular science. However, its safety must also be taken into consideration when exploring its industrial applications. This book explores the breadth of tellurium's applications, outlines strategies for industrial use, and describes the safety concerns of this element.